Promoting Learners’ Skill in Composing Poetry Using Contextual Teaching and Learning (CTL) Approach - Emon Candra; Khermarinah Khermarinah; Randi Randi (Yayasan Karinosseff Muda Indonesia, 2022)
This research was aimed to promote the quality of learners’ skills in composing poetry through the implementation of contextual teaching and learning approach towards the second grade students of SMP Negeri 05 Bengkulu City. It was designed by implementing a qualitative approach. The object of this research was the learners’ skills in writing poetry. In this research, the researchers used observation, interview, and documentation as the data collection technique and triangulation as the data validity technique. The data validity technique included triangulation of source, technique, and time. The data analysis technique consisted of several steps: 1) Data Reduction, 2) Data Display, 3) Withdrawal Conclusion and Verification, 4) Final Conclusion. The result of this research revealed that the implementation of a contextual teaching and learning approach was able in promoting the learners’ skills in writing poetry. It could be understandable as this approach enabled the learners to compose poetry effortlessly.